IMPLEMENTASI KEBIJAKAN PENERTIBAN PEDAGANG KAKI LIMA DI KELURAHAN CIBADAK KECAMATAN CIBADAK KABUPATEN SUKABUMI - Arie Melani Purbasari Melani (STISIP Widyapuri Mandiri, 2023)
Based on the results of observations , the researcher was interested to researching because there were several problems, such as insufficient resources, seen from the unavailability of relocation and the lack of number of policy implementing officers, lack of understanding and awareness of the rules. The research used a qualitative approach and descriptive method, using non-probability sampling techniques and purposive sampling and snowball sampling methods. The research location is in Cibadak Village, Cibadak District, Sukabumi Regency. The subjects of the study were 4 (four) people, namely the Cibadak Village Head, the Public Order and Peace Section, and the street vendors consisting of 2 (two) people. Data collection techniques are in the form of participatory observation and in-depth interviews as well as collecting other data relevant to in-depth research. The results show that the parameters and policy objectives are clear, the resources are not adequate, the characteristics of the implementing agents are not optimal, the attitudes or dispositions of the implementers are not optimal, communication between organizations is good, the economic, social and political environment is not yet supportive. The Government trying to overcome obstacles in the process of Implementing the Policy for Controlling Street Vendors in the Cibadak Village by giving regular appeals to street vendors to be orderly, and efforts to provide relocation land.